Why De Minimis is a Defence: A Reply to Professor Coughlan - Fehr, Colton (McGill Law Journal / Revue de droit de McGill, 2021)
Professor Coughlan maintains that the maxim de minimis non curat lex—the law does not concern itself with trifles—ought not be recognized as a criminal defence. He contends that the defence is redundant in light of existing principles of statutory interpretation, alternative defences to challenge improper decisions to bring charges, and the availability of an absolute discharge at sentencing. He further suggests that utilizing the de minimis defence is no different than allowing a constitutional exemption which has explicitly been prohibited by the Supreme Court of Canada. In response, I maintain that Coughlan improperly conceptualizes the de minimis defence as a challenge to prosecutorial discretion. In my view, the defence serves to prevent judges from finding an accused guilty where the consequences would be grossly disproportionate to the harm caused by the offence. Such proceedings should be stayed because the grossly disproportionate effects arise by virtue of instituting criminal process, not imposing punishment. Although the de minimis defence and constitutional exemptions both exempt accused from statutes, the latter are problematic because they conflict with statutory intent. The same cannot be said of defences as the legislature passes offences with knowledge that they will be circumscribed by defences.